The Influence of Commitment, Performance, and Job Satisfaction of Lecturers on Their Work Adjustment at Private Islamic Religious Higher Education Institutions in Riau Province - Azan, Khairul; Yamin, Martinis; Jamaluddin (International Journal of Social Science and Religion (IJSSR), 2025)
This study aims to describe the lecturers’ ability to adapt to their work environment, which is vital for ensuring institutional effectiveness and the overall quality of higher education. This study investigates how lecturers’ commitment, performance, and job satisfaction influence their work adjustment. Employing a quantitative research design with a survey method, data were collected from a sample of university lecturers and analyzed using Statistical Package for the Social Sciences (SPSS 25.0) to assess direct and indirect relationships among the variables. The results reveal several significant findings: commitment and performance each substantially directly affect work adjustment, both individually and jointly. Commitment and performance also significantly influence job satisfaction, both independently and simultaneously. Furthermore, job satisfaction has a strong direct impact on lecturers’ work adjustment. Commitment, performance, and job satisfaction together contribute significantly to work adjustment. The analysis also shows that commitment indirectly affects work adjustment through job satisfaction, while the indirect effect of performance through job satisfaction is not statistically significant. These findings emphasize the importance of fostering commitment and performance to enhance job satisfaction and facilitate work adjustment. Job satisfaction also mediates, reinforcing its strategic value in academic human resource development.